2013
DOI: 10.1039/c3an36761d
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Raman spectroscopy of oral buccal mucosa: a study on malignancy associated changes (MAC)/cancer field effects (CFE)

Abstract: Occurrence of metachronous and synchronous secondary tumors in oral cavities has been associated with poor prognosis and decreased 5-year disease-free survival rates. The origin of secondary tumors in the oral cavity has been primarily attributed to cancer field effects (CFE) or malignancy-associated changes (MAC) in uninvolved areas. Classification of normal, cancerous and pre-cancerous oral lesions by in vivo Raman spectroscopy (RS) has already been demonstrated. In the present study, MAC/CFE in oral buccal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
109
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(112 citation statements)
references
References 35 publications
3
109
0
Order By: Relevance
“…RS has also shown to detect age-related physiological conditions and even subtle cancer-¯eld e®ects (CFE). 25,26 However, these two studies undertaken in the present laboratory established the potential of RS for only buccal mucosa subsite. Additionally, two recent studies have also investigated possibility of surgical demarcation using tumor and normal biopsies.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…RS has also shown to detect age-related physiological conditions and even subtle cancer-¯eld e®ects (CFE). 25,26 However, these two studies undertaken in the present laboratory established the potential of RS for only buccal mucosa subsite. Additionally, two recent studies have also investigated possibility of surgical demarcation using tumor and normal biopsies.…”
Section: Introductionmentioning
confidence: 78%
“…25 This system consists of a diode laser (Process Instruments, USA) of 785 nm wavelength as the excitation source, a high e±ciency (HE) spectrograph with¯xed 950 gr/mm grating coupled with a CCD (Synapse). The instrument has no movable parts and the spectral resolution as speci¯ed by the manufacturer is 4 cm À1 .…”
Section: Raman Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…13 Furthermore, Singh et al demonstrated malignancy associated changes in the buccal mucosa probed by Raman in at risk patient groups from tobacco exposure. 14 Although Raman has good chemical specificity, it is hindered by the low probability of an inelastic scattering event. From one million photons interacting with a molecule, there may only be one photon that is inelastically scattered.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…Since first finding of CFE from oral cancers in 1953 [1], studies related to CFE have been gradually increased [2,3]. While other techniques including microscopy, polymerase chain reaction (PCR), and immunohistochemistry were utilized to study CFE [3][4][5][6], Raman spectroscopy has been spotlighted as a useful tool since it has been shown that the spectroscopy can detect changes that are insensitive to histological evaluation implying that chemical changes are not local and proceed earlier than anatomical or physical changes [7][8][9]. Such studies proved the ability of Raman spectroscopy as a dominant candidate for a sensitive and minimally invasive optical biopsy tool.…”
Section: Introductionmentioning
confidence: 99%